Neural Mechanisms Involved in Hypersensitive Hearing: Helping Children with ASD Who Are Overly Sensitive to Sounds. (28th December 2015) - Lucker, Jay R.; Doman, Alex
Abstract : Professionals working with children diagnosed with autism spectrum disorder (ASD) may find that these children are overly sensitive to sounds. These professionals are often concerned as to why children may have auditory hypersensitivities. This review article discusses the neural mechanisms identified underlying hypersensitive hearing in people. The authors focus on brain research to support the idea of the nonclassical auditory pathways being involved in connecting the auditory system with the emotional system of the brain. The authors also discuss brain mechanisms felt to be involved in auditory hypersensitivity. The authors conclude with a discussion of some treatments for hypersensitive hearing. These treatments include desensitization training and the use of listening therapies such as The Listening Program.